Tauopathy induces degeneration and impairs regeneration of sensory nerves in the cornea. (February 2022) - Li, Shengguo; Shi, Shuizhen; Luo, Ban; Xia, Fan; Ha, Yonju; Merkley, Kevin H.; Motamedi, Massoud; Zhang, Wenbo; Liu, Hua
Abstract: The cornea is transparent and innervated by a dense collection of sensory nerves originating from the ocular branch of the trigeminal nerve. This study was designed to comprehensively analyze alterations of corneal sub-basal nerve plexus in a mouse model of tauopathy (P301L transgenic mice) to test the possibility of using corneal nerves as a biomarker for tauopathy. Corneal sensitivity, thickness and epithelial wound healing were measured non-invasively by aeshesiometer, optical coherence tomography and fluorescein staining, respectively. Tau, corneal nerves and immune cells were examined by immunohistochemistry or Western blot. At the early stage of tauopathy, although corneal sensitivity, thickness and nerve fiber density were not greatly altered, corneal nerve abnormalities were observed in the peripheral region of young P301L mice. With aging, the density of abnormal nerves increased, while corneal sensitivity, epithelial thickness, nerve fiber density and length decreased in middle-aged P301L mice compared with WT mice. After corneal epithelial injury in young mice, no difference in reepithelialization was observed between two groups of mice, however, the regeneration of corneal nerves in P301L mice lagged behind WT mice, which was reflected by delayed recovery of corneal sensitivity, decreased corneal nerve density and length and density of CD45 + dendriform cells in P301L mice. In conclusion, our data provide compelling evidence that corneal nerves were changed in a mouse model of tauopathy in an age-dependent manner. Moreover, tau overexpression impairs corneal nerve regeneration. These results suggest that cornea may serve as a promising ocular site for the early diagnosis of tauopathy. Highlights: Corneal nerve abnormalities were observed in the peripheral region of young P301L mice at the early stage of tauopathy. With aging, corneal sensitivity, epithelial thickness, nerve fiber density and length decreased in middle-aged P301L mice. Corneal nerve regeneration was impaired at the early stage of tauopathy. Our results suggest that cornea may serve as a promising ocular site for the early diagnosis of tauopathy.